Are small towns doomed to decline? The case of a post-socialist CEE country. Issue 8 (17th November 2021) - Cole, David; Svidroňová, Mária Murray
ABSTRACT: It is a common belief that small towns of formerly socialist countries of Central and Eastern Europe (CEE) are suffering a substantial decline due to the better offerings in bigger metropolitan areas and in western countries. This belief has been reinforced by a long transformation process: firstly, the transition from a command economy to capitalism and secondly, the move from manufacturing to service. To investigate this issue, a concentrated research on one territory was conducted, which gives a more intimate picture of the status of rural municipalities in a typical post-communist area of CEE. This information was compared to secondary historical and current data concerning economics, infrastructure, and demographics giving us a picture of the municipalities' viability by creating a multi-criteria analysis. This research indicates that small towns are not suffering precipitous declines, which is a common belief.